Politics and Testimony. Political Implications of Jan Patočka’s and Edith Stein’s Testimony - Szalay, Mátyás (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
I investigate the complex relationship between politics and philosophy by focusing on the notion of testimony. I argue that there is a necessary and fruitful tension between sapiential and political life. Testimony is characterized here as a free value-response in an intersubjective relation that requires empathy on both sides of the communication. This act of affirming a truth or value goes beyond the limits of prudent self-realization and self-preservation: authentic testimony requires some kind of self-sacrifice. I contrast this general image of testimony to Jan Patočka’s interpretation of «care for the soul». Patočka, by following the early Husserl’s renewal of philosophy, managed to establish and to preserve the harmony between theory and praxis even during persecution of the communist regime. His courageous acts come close to and illuminate the testimony of Edith Stein, who set the measure for philosophical authenticity and self-donation. The comparison of these two testimonies helps to elaborate the notion of exemplary sapiential life — a highly relevant notion for politics.